The exploitation of authentic tasks in speaking classes for English non-major freshmen at Hanoi University of Industry = Nghiên cứu việc khai thác các hoạt động thực tiễn trong lớp học nói cho sinh viên năm thứ nhất khối không chuyên Anh ở Trường Đại học - Nguyễn, Thị Hoa (University of Languages and International Studies, 2017)
M.A. Thesis English teaching methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2011